Role of Platelets in Neonatal Necrotizing Enterocolitis - Maheshwari, Akhil (Pediatr Res, 2020)
Necrotizing enterocolitis (NEC) is an inflammatory bowel necrosis of premature infants, and is a leading cause of morbidity and mortality in infants born between 23–28 weeks of gestation. Fifty to 95% of all infants with NEC develop thrombocytopenia (platelet counts <150 × 10(9)/L) within 24–72 hours of receiving this diagnosis. In many patients, thrombocytopenia is severe and is treated with one or more platelet transfusions. However, the underlying mechanism(s) and biological implications of NEC-related thrombocytopenia remain unclear. This review presents current evidence from human and animal studies on the clinical features and mechanisms of platelet depletion in NEC. Anecdotal clinical experience is combined with evidence from laboratory studies and from an extensive literature search in databases PubMed, EMBASE, Scopus, and the electronic archives of abstracts presented at the annual meetings of the Pediatric Academic Societies. To avoid bias in identification of existing studies, key words were short-listed prior to the actual search both from anecdotal experience and from PubMed’s Medical Subject Heading (MeSH) thesaurus.